Environments of Health and Disease in Tropical Africa before the Colonial Era - (:unkn) unknown (My University, 2022)
A long-standing narrative that has its origins, in part, in early modern European travel narratives entwines Africa, diseased environments, and death. By probing these seventeenth-century narratives as historical sources and reflecting critically on their contents, this chapter reveals a Eurocentric “smokescreen” that hides a much more complex picture. The African understanding of the “environment” – and disease causation – was far more extensive than we think today: it embodied the physical landscape and the spiritual and social realms. Managing the multiple spheres that comprised the environment meant that pre-modern Africans had developed a complex variety of disease mitigation techniques, each targeting the suspected origin of disease. The chapter also includes an exploration of the author’s working hypothesis about the making, demise, or subsistence of malaria and plague in selected regions of the African continent’s environment, demonstrating how working cross-disciplinarily and bringing together evidence from the humanities and the sciences – including research on ancient DNA – allows us to slowly build a clearer picture of the intricate relationship between diseases and the environment in the African past.
Keywords: African Research